IDENTIFIKASI IKM (INDUSTRI KECIL MENENGAH) KECAMATAN JEPARA KABUPATEN JEPARA - Agus Sarwo Edy Sudrajat; Nella Ardiantanti Siregar (Indonesian Journal of Spatial Planning, 2021)
Over time, The number of IKMs which continued to increase and were not accompanied by data collection was what ultimately caused problems. The lack of awareness to register a business that is owned is still one of the causes. In fact, this is very important to do. Seeing the above phenomenon makes us aware of the importance of data collection on IKM, especially those in Jepara District, Jepara Regency. This research method uses a qualitative approaches. The analysis technique used is descriptive analysis and normative analysis. The process of validation and data collection is based on the indocators contained in the querstionnaire. 9 indicators in data collection, namely IKM business actors, Business Permits, Type Of Industry, KBLI, Number Of Workers, Raw Materials, Working Capital, Production Capacity, and Investment. The final result of the activity is a data master document for IKM in Jepara District which is compiled in order to support the smooth implementation of goods / services procurement.